Camphor burns of the palm and non-suicidal self-injury: An uncommonly reported, but socially relevant issue - Ravi Kumar Chittoria; Devi Prasad Mohapatra; Meethale Thiruvoth Friji; S. Dinesh Kumar; Arjun Asokan; Sandhya Pandey (Indian Journal of Plastic Surgery)
Camphor is a waxy white sublimating chemical derived from natural as well as synthetic sources and widely used in various communities worldwide for a number of medicinal, culinary, and religious reasons. Camphor is burnt as an offering to God in many religious communities. We report three incidences of self inflicted injury from burning camphor on the palm resulting in full thickness burns. Non-suicidal self-injury is socially unacceptable destruction or alteration of body tissue when there is no suicidal intent or pervasive developmental disorder and we have explored an association between this and burn injury. This report also highlights the unique social and cultural pattern of this burn injury and the importance of psycho-therapeautic help for these victims.